Ruthenium‐Catalyzed Reductive Arylation of N‐(2‐Pyridinyl)amides with Isopropanol and Arylboronate Esters. (11th December 2018) - Ronson, Thomas O.; Renders, Evelien; Van Steijvoort, Ben F.; Wang, Xubin; Wybon, Clarence C. D.; Prokopcová, Hana; Meerpoel, Lieven; Maes, Bert U. W.
Abstract: A new three‐component reductive arylation of amides with stable reactants (iPrOH and arylboronate esters), making use of a 2‐pyridinyl (Py) directing group, is described. The N‐Py‐amide substrates are readily prepared from carboxylic acids and PyNH2, and the resulting N‐Py‐1‐arylalkanamine reaction products are easily transformed into the corresponding chlorides by substitution of the HN‐Py group with HCl. The 1‐aryl‐1‐chloroalkane products allow substitution and cross‐coupling reactions. Therefore, a general protocol for the transformation of carboxylic acids into a variety of functionalities is obtained. The Py‐NH2 by‐product can be recycled.